Pengaruh Tingkat Inflasi, Tingkat Suku Bunga, Nilai Tukar Rupiah (USD), dan Indeks Produksi Industri Terhadap Pertumbuhan Sukuk Korporasi di Indonesia - Muthia Aisyah; Andri Soemitra; Khairina Tambunan (STIKes Ibnu Sina Ajibarang, 2024)
The company began to develop the sharia financial industry, namely corporate Sukuk, which began to experience quite good growth in Indonesia. This is proven by the existence of companies that have issued sukuk. Compared to government sukuk or conventional bonds, corporate sukuk is still relatively slow, but its growth is increasing every year. In this research, the variables that can influence economic activity are the inflation rate, interest rate, Rupiah exchange rate (USD), and industrial production index. This research aims to analyze the growth of corporate sukuk in Indonesia. The research method used is a quantitative method with a descriptive approach. With data analysis techniques using multiple linear regression models. The research results show that the inflation rate and Rupiah exchange rate (USD) influence the growth of corporate sukuk in Indonesia. The results of the research on Interest Rates and the Industrial Production Index show that the results have no effect on Sukuk Growth in Indonesia. Meanwhile, the research results simultaneously show that the variables of inflation rate, interest rate, rupiah exchange rate (USD), and industrial production index influence the growth of sukuk in Indonesia.